Total phenolic content and antioxidant capacity of basil (Ocimum basilicum L.) leaves from different locations - Aburigal, Yasmin Adam Ali; Mirghani, Mohamed Elwathig Saeed; Elmogtaba, Elfadl Y.; Sirible, Awatif A. M.; Hamza, Nada; Hussein, Ismail H. (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
The present study was carried out to determine the antioxidant activity and total phenolic content of Ocimum basilicum collected from different regions of the world. The accession V1 is from Sudan, V2 from Iraq, V3 from Germany, V4 from Thailand, V5 from Russia and V6 from Maldives. The extracts from six basil accessions were analysed for their DPPH free radical scavenging activity and their total phenolic content (TPC). The results suggest that the highest antioxidant activity was found in V6 (from Maldives) and the lowest antioxidant activity was found in V4 (from Thailand). The highest amount of phenolic content was found in V6 (from Maldives) and the lowest phenolic content was found inV4 (from Thailand). This study shows that basil is a good source of free-radical scavenging compounds that have their traditional medicinal applications.